The Response of Shallow Groundwater Levels to Soil Freeze–Thaw Process on the Qinghai‐Tibet Plateau. Issue 4 (19th November 2018) - Dai, Licong; Guo, Xiaowei; Du, Yangong; Zhang, Fawei; Ke, Xun; Cao, Yingfang; Li, Yikang; Li, Qian; Lin, Li; Cao, Guangmin
Abstract: The Qinghai‐Tibet plateau has the world's largest area of seasonally frozen ground. Here, shallow groundwater displays behavior that is distinct from that elsewhere in the world. In the present study, we explore the seasonal and interannual variation of the shallow groundwater levels from 2012 to 2016, and attempt to quantitatively evaluate the relative influences of individual driving factors on the shallow groundwater levels based on boosted regression trees. The results show that: (1) on a seasonal scale, the groundwater levels were characterized by a double peak and double valley relationship, while on an interannual scale the groundwater levels showed a slightly downwards trend from 2012 to 2016; and (2) during the frozen period, the seasonal variation of groundwater levels was determined by mean air temperature through its effect on the soil thaw–freeze process, accounting for 53.15% of total variation. Meanwhile, ET0 and rainfall exerted little impact on the seasonal variation of groundwater levels, which might be attributed to the aquitard of frozen soil that impedes the exchange between surface water and groundwater. Moreover, there was a lag between groundwater levels and soil freezing–thawing. During the non‐frozen period, the mean air temperature was again the most important factor impacting the variation of groundwater levels, through its effect on ET0, and accounted for 40.75% of total variation, while rainfall had little effect on groundwater levels when rainfall intensity was less than 12 mm/day. These results will benefit predictions of future trends in groundwater levels within the context of global warming. Abstract : Article impact statement : This research will benefit predictions of future trends in groundwater level within the context of global warming.